Female Dynamics in Authorship of Scientific Publications in the Public Library of Science: A 10-year Bibliometric Analysis of Biomedical Research - Panagiotis Giannos; Konstantinos Katsikas Triantafyllidis; Maria Paraskevaidi; Maria Kyrgiou; Konstantinos S. Kechagias (MDPI AG, 2023)
Women are generally underrepresented in science, technology, engineering, and mathematics (STEM). As scientific production reflects scholarly impact and participation in the scientific process, the number of journal publications forms a pertinent measure of academic productivity. This study examined the prevalence and evolution of female representation in prominent author positions across multidisciplinary biomedical research. Publications from seven exemplar cross-specialty journals of the Public Library of Science (PLoS Medicine, PLoS Biology, PLoS One, PLoS Computational Biology, PLoS Genetics, PLoS Pathogens, and PLoS Neglected Tropical Diseases) between January 2010 and December 2020 were extracted from Web of Science. Using Genderize.io, the gender of authors from their first names was estimated using a 75% threshold. The association between female prevalence in first and last authorship and journal was evaluated using a binary logistic regression, and odds ratios were estimated against a 50:50 reference on gender. In 266,739 publications, 43.3% of first authors and 26.7% of last authors were females. Across the ten-year period, female first authorship increased by 19.6% and last authorship by 3.2%. Among all journals, PLoS Neglected Tropical Diseases had the greatest total proportion of female first authors (45.7%) and PLoS Medicine of female last authors (32%), while PLoS Computational Biology had the lowest proportion in these categories (23.7% and 17.2%). First authors were less likely to be females in all PLoS journals (p < 0.05) except for PLoS Neglected Tropical Diseases (odds ratio: 0.84, 95% confidence interval: 0.71-1.00), where the odds of female authorship were not significantly different (p = 0.054). Last authors were not more likely to be females in all PLoS journals (p < 0.001). Overall, women still appear underrepresented as first authors in biomedical publications and their representation as last authors has severely lagged. Efforts towards gender equality in scholarly authorship will contribute to the representation of women in biomedical research and ensure that their potential is not lost.